Encapsulation of orange terpenes investigating a plasticisation extrusion process. (June 2015) - Tackenberg, Markus W.; Krauss, Ralph; Schuchmann, Heike P.; Kleinebudde, Peter
Abstract Extrusion is widely used for flavour encapsulation. However, there is a lack of process understanding. This study is aimed at improving the understanding of a counter rotating twin screw extrusion process. Orange terpenes as model flavour, maltodextrin and sucrose as matrix materials, and a water feed rate between 4.0% and 5.7% were applied. Product temperatures < 80 °C and specific mechanical energy inputs <260 Wh/kg resulted. Amorphous and partly crystalline samples were obtained. The loss of crystalline sucrose was linked to a dissolution process of the sugar in the available water amount. Melting of the excipients did not arise, resulting in a plasticisation extrusion process. Maximally 67% of the flavour was retained (corresponding to a 4.1% product flavour load). The flavour loss correlated with insufficient mixing during the process and flavour evaporation after extrusion. Based on these results, recommendations for an improved encapsulation process are given.